Association of Plasma Fibrinogen and Insulin Resistance in Women with Gestational Diabetes Mellitus - S, Mahjabeen; S, Selim; M, Mustari; MH, Rajib; AKMS, Rahman; M, Fariduddin; MA, Hasanat (Archives of Clinical and Biomedical Research, 2022)
Gestational diabetes mellitus (GDM) is thought to be developed as a consequence of high insulin resistance (IR). It has been proposed that IR may involve in the pathogenesis of hyperfibrinogenemia in GDM. This study was aimed to evaluate the plasma fibrinogen levels and its association with insulin resistance in GDM. This cross sectional study was performed with 44 GDM women and 44 pregnant women with normal glucose tolerance (NGT) at or after 24 weeks of their gestation. Glucose was measured by glucose oxidase method, fasting insulin was measured by chemiluminescent immunoassay and plasma fibrinogen was measured by STA-fibrinogen kit with an automated coagulation analyzer. GDM women had significantly increased age and higher BMI than pregnant women with NGT (p=0.008). Plasma fibrinogen level was significantly higher in GDM (p<0.001). Fasting insulin level and Homeostasis Model Assessment of Insulin Resistance [HOMA-IR] were also significantly higher in GDM (p<0.001). Fibrinogen showed positive correlation with fasting insulin level (r=0.470, p<0.001) as well as with HOMA-IR (r=0.470, p<0.001) in GDM. Using HOMA-IR at cut-off value 2.89, it was observed that a significant number of GDM women had higher HOMA-IR values than pregnant women with NGT (p=0.002) and GDM women with HOMA-IR values ≥2.89 had significantly higher fibrinogen values (p=0.002). Gestational diabetes mellitus is associated with higher plasma fibrinogen level and increased insulin resistance, indicating a state of hypercoagulability than that of pregnant women with normal glucose tolerance. There is a clear association between hyperfibrinogenemia and insulin resistance.